Distribuição espacial de espécies da Floresta Ombrófila Mista na FLONA de Irati, Paraná - Pottker, Gustavo Sartori (2012)
The analysis of trees spatial pattern is a logical way for understanding phenomena such as competition and environmental preferences of forest species. The objective of this research was to unveil factors related to the establishment of the forest, as well as describe and analyze the environmental preferences of some species employing Spatial Statistics. For this purpose, it was used data from the inventory of the protected area Irati`s FLONA, containing the locations of the trees in an area of 25 hectares. Seven species were selected, for which the McGuinnes aggregation index was presented as the traditional approach to assess the spatial pattern of species. Following this analysis, the estimate of first order intensity was obtained and confronted with altitude and soil types` information. In a second moment, the intraspecific relationships were studied with the inhomogeneous Ripley`s K function, being these results compared with ecological characteristics of the species, such as seed dispersal, tolerance to shadowing and allelopathic effects. Through the study of species intensities, we could conclude that Ocotea odorifera and Ocotea porosa species were clear ly affected by thealtitude. Cedrela fissilis and Casearia decandra have demonstrated preferences for certain types of soil. Lastly, coincidences in the occupation of space were observed between Nectandra grandiflora and Araucaria angustifolia; the opposite was shown between Ocotea odorifera and Ilex paraguariensis, which tended to occupy distinct regions of the sampled area. With respect to the Ripley`s K function, it was verified mostly aggregation for Araucaria angustifolia, Ilex paraguariensis and Nectandra grandiflora; regularity for Ocotea porosa; and randomness in the spatial pattern of Casearia decandra, Ocotea odorifera and Cedrela fissilis. The techniques were adequate to describe the spatial pattern of species, complementing the McGuinnes index, which is susceptible to the size of sampling units.